PENGARUH PENAMBAHAN GLISEROL DAN CMC (Carboxyl Methyl Cellulose) TERHADAP KARAKTERISTIK BIODEGRADABLE FILM BERBASIS SELULOSA KULIT BUAH PINANG (Areca catechu L) EFFECT OF GLYCEROL AND CMC (Carboxyl Methyl Cellulose) ADDITION ON BIODEGRADABLE FILM CHARACTERISTIC OF ARECA NUT-PEEL (Areca catechu L) CELLULOSE BASED - Sela Julita; Zulferiyenni Zulferiyenni; Dewi Sartika; Dyah Koesoemawardani (Jurnal Agroindustri Berkelanjutan, 2023)
Biodegradable film is an environmentally friendly plastic replacement packaging. Areca fruit peel has the potential to make biodegradable film because it contains high cellulose, which is 34.18%. This study aims to determine the effect of glycerol addition on the characteristics of areca nut peel-based biodegradable film, to determine the effect of CMC on the characteristics of areca nut peel-based biodegradable film, and to determine the interaction of glycerol and CMC to produce the best characteristics of areca nut peel-based biodegradable film. The study was arranged in RAKL with 2 factors and 3 replications. The first factor was the addition of glycerol with concentrations of 0.5% (G1), 1% (G2), and 1.5% (G3), and the second factor was the addition of CMC consisting of concentrations of 1% (C1), 2% (C2), and 3% (C3). Areca fruit peels were dried, mashed, filtered, soaked using 2.5% NaOH, hydrolyzed using 2% H2O2, and mixed with other ingredients. The data obtained were analyzed for variance and further tested with the Least Significant Difference Test (BNT) at the 5% level. The best research results were obtained in the interaction of 1% glycerol and 3% CMC treatment with a tensile strength of 71.87 MPa, percent elongation value of 26.27%, a thickness of 0.32 mm, water vapour permeability of 7.41 g/m2/hour, and biodegradability for 28 days.